2020
DOI: 10.1136/bmjopen-2020-040178
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of burnout in Hong Kong doctors up to 20 years post-graduation: a cross-sectional study

Abstract: ObjectiveTo estimate the prevalence and severity of burnout and explore the factors associated with burnout among Hong Kong medical graduates up to 20 years post-graduation.DesignCross-sectional survey.SettingHong Kong.ParticipantsDoctors who graduated from the University of Hong Kong between 1995 and 2014.Primary and secondary outcome measuresBurnout as measured by the Copenhagen Burnout Inventory (CBI), alcohol consumption as measured by the Alcohol Use Disorders Identification Test Version C, lifestyle beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 49 publications
2
25
3
Order By: Relevance
“…The mean client-related score was 49.0 ± 22.3, slightly below the score of 50 that constituted the threshold for burnout. These scores were higher than in the previous study performed in Hong Kong by Ng et al, 10 which showed mean CBI scores of 57.4 ± 21.4 (personal), 48.9 ± 7.4 (work-related), and 41.5 ± 21.8 (client-related). Moreover, when compared with studies worldwide that used the CBI to measure burnout in doctors, 15,16,18,22 the levels of burnout in the present study were among the highest.…”
Section: Burnout Among Doctors In Hong Kong and Worldwidecontrasting
confidence: 76%
See 2 more Smart Citations
“…The mean client-related score was 49.0 ± 22.3, slightly below the score of 50 that constituted the threshold for burnout. These scores were higher than in the previous study performed in Hong Kong by Ng et al, 10 which showed mean CBI scores of 57.4 ± 21.4 (personal), 48.9 ± 7.4 (work-related), and 41.5 ± 21.8 (client-related). Moreover, when compared with studies worldwide that used the CBI to measure burnout in doctors, 15,16,18,22 the levels of burnout in the present study were among the highest.…”
Section: Burnout Among Doctors In Hong Kong and Worldwidecontrasting
confidence: 76%
“…9 Another survey also suggested that burnout was prevalent among doctors in Hong Kong, but it only included graduates from one medical school in Hong Kong. 10 Hence, this study aimed to evaluate the prevalence of burnout in the Hong Kong medical and dental workforce by administering standardised questionnaires to a broad population of residentsin-training and doctors within 10 years of their specialist registration. The study also explored wellbeing among doctors in terms of job satisfaction, depression, lifestyle behaviours, and factors associated with these states.…”
Section: 香港年青醫生工作過度勞累和身心健康的全港 橫斷面調查mentioning
confidence: 99%
See 1 more Smart Citation
“…Doctors with more than 60 working hours per week and doing night shift would be expected to have a significantly much higher prevalence of burnout however in this study, however, there was no significant differences in the prevalence of burnout among them. The finding was contradicted with other studies done in various countries where long working hours and night shift were significantly associated with burnout [33][34][35] . The contradiction might be due to that those medical officers had already been able to cope with the long working hours and night shift as they have been experienced during their housemanship training years 36 .…”
Section: Resultscontrasting
confidence: 87%
“…In this issue of Hong Kong Medical Journal, Kwan et al 1 report the results of a survey of young doctors in Hong Kong (residents in training and specialists within 10 years of registration), showing high rates of burnout using the Copenhagen Burnout Inventory (73% reported personal burnout; 71% reported work-related burnout; and 55% reported client-related burnout) and depression using the Patient Health Questionnaire-9 (21%). Although the worldwide prevalence of burnout among medical professionals is increasing, 2 the local situation in Hong Kong 1,3,4 is alarming and the Hong Kong Academy of Medicine is committed to tackling this problem. A Well-being Charter has been promulgated in confirmation of the commitment of the Academy and its 15 constituent Colleges.…”
mentioning
confidence: 99%